KONSTRUKSI SEKSUALITAS PEREMPUAN DALAM KEINDAHAN DAN KESEDIHAN KARYA YASUNARI KAWABATA - Pranoto, Agung; Damayanti, Rini (Universitas Wijaya Kusuma Surabaya, 2019)
This research examines the construction of female sexuality in the novel the beauty and sorrow of the works of Yasunari Kawabata. This research is qualitative research that does study of novel the beauty and sorrow of the works of Yasunari Kawabrata. The method used is the deskiptif method that is collecting data, clarification of data, manipulate data, and interpret the data in accordance with the theory that was used at the time the research was conducted. In the novel the beauty and sorrow of the works of Yasunari Kawabata, reflecting the construction of female sexuality. The construction of female sexuality that, first, the novel represents the female body through the figures. The representation of the female body in the text of the novel disegmentasikan by displaying the marker women sexy. Second, the representation of female sexual desire in the novel beauty and Sadness is presented through the desire character Otoko and Keiko to transmit sexual desires with her partner. Third, representations of female sexuality in the relation of beauty and sadness, by Yasunari Kawabata was still predominantly on the male as the subject.